The postmodern history reader - Jenkins, Keith (Routledge, 1997)
The Postmodern History Reader is the most comprehensive collection of influential texts on historiography and postmodernism yet compiled. Keith Jenkins expertly selects from the books and journal articles across the whole historiographical range that have been key to the transforming debates.